The Influence Of Viral Marketing And Electronic Word Of Mouth On Purchase Decisions Of Kula Products On Tiktok Shop (A Study On Generation Z In Medan City) - Marbun, Yuana Widya Angeline Br; Siregar, Onan Marakali (UNIVED Press, 2026)
The Indonesian beauty industry, particularly the lip product segment, is rapidly expanding. One emerging local brand, KULA, utilizes TikTok Shop and relies on viral marketing and electronic word of mouth (eWOM) to attract Generation Z consumers. This study examines the influence of viral marketing and eWOM on purchase decisions of KULA products among TikTok users in Medan. A quantitative research method with an associative approach was applied, involving 96 purposively selected respondents who had previously purchased KULA products. Data were collected through online and offline questionnaires and analyzed using multiple linear regression. The findings show that both viral marketing and eWOM significantly affect purchase decisions, individually and jointly. Viral marketing emerged as the stronger predictor, while eWOM also showed a notable positive effect. These results highlight the strategic value of social media-based marketing in shaping Gen Z’s purchasing behavior, especially in digital commerce platforms like TikTok Shop.